The Importance of the Creative Sector in the Development of Cities and Regions - Pięta-Kanurska, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Creative economy is formed and develops most rapidly in urban areas, and increasingly in the surrounding regions. It is based on the creative sector. Creative industries have become a key driving force in the economy by promoting innovation and building a modern information society.